THE CORRELATION BETWEEN PARTICIPATION OF STUDENTS IN PEER ASSISTED LEARNING (PAL) AND OBJECTIVE STRUCTURED CLINICAL EXAMINATION (OSCE) SCORES IN FACULTY OF MEDICINE UNIVERSITAS GADJAH MADA - , CAMELIA PONDRA DEWANTARIE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The result from OSCE in Faculty of Medicine UGM showed that approximately 30% students failed in OSCE. This could be caused by many factors and one of them could be due to lack of participation of students in Peer Assisted Learning (PAL). Objective: The objective of this study is to determine whether there is any correlation between participation of students in PAL and their OSCE scores in Faculty of Medicine Universitas Gadjah Mada. Methods: Ninety-two (92) fourth-year medical students from international programme, who use PAL as one of their learning methods (Response Rate = 86.79%) were asked to reflect and fill in the questionnaires about PAL and OSCE, based on their experiences during PAL and OSCE. Data obtained from the questionnaires were measured and analyzed quantitative and qualitatively to know whether there is any correlation between participation of students in PAL and OSCE scores. Results: In this study, it is found that correlation between participation of students in PAL and OSCE scores is 0.098 with P = 0.353. Besides, there are also factors that could influence OSCE results beside PAL, which are individual preparation, scheduled skills laboratory, and situation during OSCE, including anxiety of students and technical reasons. Conclusion: The result suggests that there is no significant correlation between participation of students in PAL and their OSCE scores.